"Mobilität in Deutschland 2002" im Wochen- und Jahresgang. Zur zeitlichen Schwankung von Mobilitätskennwerten. - Rümenapp, Jens; Seiler, Ines; Steinmeyer, Imke (Deutscher Verkehrs-Verl., 2006)
Die Daten der Erhebung "Mobilität in Deutschland 2002" bieten Grundlagen und Anknüpfungspunkte für eine breite Palette wissenschaftlicher und ökonomischer Fragestellungen. Im Rahmen des BMVBS-Forschungsprojekts "Auswertung der Erhebung Mobilität in Deutschland 2002 in Bezug auf Wochen- und Jahresgang" wurden wichtige Erkenntnisse zu zeitlichen Schwankungen von Mobilitätskennwerten gewonnen. Wochentagstypen und Jahresgangphasen mit annähernd gleicher Charakteristik wurden identifiziert, Korrekturfaktoren zwischen den Kennwerten einzelner Wochentage, Wochentagstypen und Jahresgangphasen ermittelt und Empfehlungen für die Festlegung von Erhebungszeiträumen formuliert. difu

Data gleaned from the investigation of Germany's mobility in the year 2002 offers a suitable base for looking into science- and economy-related matters. Based on a BMVBS research project (MID 2002) that covers weekly and annual modules, it has been possible to identify homogeneous mobility characteristics for typical weekdays and years. Also, corrective elements relating to specific days of the week, different types of weekdays, and yearly phases can be establishing while it is possible to offer recommendations for specific periods of investigation. The most important conclusions can be summarized as follows: Time-sensitive variations (relating to weekly or yearly cycles) can be pin-pointed but are largely dependent on certain mobility- and time-related factors since they have to take into account - or disregard - annual school or public holidays. (a) Weekly mobility: In order to achieve greater accuracy, it is recommended to arrange for investigations to cover an entire week. (b)Annual mobility: It is only possible to highlight important statistics-based differences for a typical month by way of comparing data for spring and summer with that for autumn and winter periods. A typical "average month" does not exist since public holidays and annual school holidays differ in each of Germany's "Länder" and are spread out over several months. It is, therefore, not possible to pinpoint a typical workday that is the same throughout the Federal Republic. difu
Keywords: Öffentlicher Verkehr; Verkehrsplanung; Mobilität; Verkehrsstatistik; Verkehrsverhalten; Forschungsprojekt; Verkehrsberechnung; Befragung; Empirische Untersuchung; Verkehrsforschung; Verkehrsbefragung; Zeitverlauf